A deep dig––hindsight on Holocene vegetation composition from ancient environmental DNA. Issue 13 (20th June 2013) - Gugerli, Felix; Alvarez, Nadir; Tinner, Willy
<x xml:space="preserve">Abstract</x> Want a glimpse at past vegetation? Studying pollen and other plant remains, which are preserved for example in lake sediments or mires for thousands of years, allows us to document regional occurrences of plant species over radiocarbon‐dated time series. Such vegetation reconstructions derived from optical analyses of fossil samples are inherently incomplete because they only comprise taxa that contribute sufficient amounts of pollen, spores, macrofossil or other evidences. To complement optical analyses for paleoecological inference, molecular markers applied to ancient DNA (aDNA) may help in disclosing information hitherto inaccessible to biologists. Parducci et al. (2013) targeted aDNA from sediment cores of two lakes in the Scandes Mountains with generic primers in a meta‐barcoding approach. When compared to palynological records from the same cores, respective taxon lists show remarkable differences in their compositions, but also in quantitative representation and in taxonomic resolution similar to a previous study (Jørgensen et al. 2012). While not free of assumptions that need critical and robust testing, notably the question of possible contamination, this study provides thrilling prospects to improve our knowledge about past vegetation composition, but also other organismic groups, stored as a biological treasure in the ground.